Formulasi dan Uji Aktivitas Antioksidan Krim Biji dan Ekstrak Etanol Daun Jambu Biji (Psidium guajava L.) sebagai Body Scrub - Putri, Noni Rahayu; Agustin, Diana; Nisa, Khairatun (Jurnal Kefarmasian Indonesia, 2022)
Ethanol extract of guava leaf (Psidium guajava L.) contains flavonoids and tannins that are potentially as an antioxidant that may inhibit the activity of free radicals.The aim of this study is to formulate a body scrub cream from ethanol extract of guava leaf (Psidium guajava L.) and test their antioxidant activity.This study used three variations of concentration of ethanol extract 70% of guava leaf (Psidium guajava L.) i.e 1,5%, 2% and 2,5%.Body scrub creams are formulated into O/W type of creams by using guava seeds as a scrub.Evaluation of preparations included organoleptic examination, homogeneity, pH, cream type, stability test, particle size distribution, dispersion test and antioxidant activity test using DPPH method. The evaluation results showed that the physical properties of cream preparations provided good results and meet the requirements of cream preparations.The results of the antioxidant activity test found that the values of IC50 for each formula was F0 (without extract) 379,58 µg / mL, F1 (1,5%) 150,78 µg/mL, F2 (2%) 137,26 µg/mL and F3 (2,5%) 125,84 µg/mL.It can be concluded that body scrub creams of ethanol extract 70% of guava leaves (Psidium guajava L.) has the potential to be developed as a cosmetic preparation that can inhibit free radicals.